2005
DOI: 10.1128/iai.73.2.1209-1213.2005
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor γ and Retinoid X Receptor Agonists Have Minimal Effects on the Interaction of Endothelial Cells withPlasmodium falciparum-Infected Erythrocytes

Abstract: Peroxisome proliferator-activated receptor ␥-retinoid X receptor (PPAR␥-RXR) agonists had minimal effects on the surface levels of CD36, intercellular cell adhesion molecule-1, or platelet-endothelial cell adhesion molecule-1 and had no effect on the cytoadherence of infected erythrocytes to either human umbilical vein endothelial cells or human microvascular endothelial cells or on malaria-induced interleukin-6 secretion from these cells. PPAR␥-RXR agonists do not significantly modify malaria-infected erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Interestingly, it was also observed in this clinical trial that the administration of Rosiglitazone led to lower parasite clearance time 145. This observation might be explained from another study, which showed that Rosiglitazone preferentially increases the expression of CD36 on macrophages146 with minimal effect on endothelial cells148 and this would potentially lead to increased phagocytosis by these cells 149. Taken together, this study shows that targeting inflammatory responses at higher exposures might indeed be protective, but these processes need to be adequately investigated.…”
Section: Taking Advantage Of Immune Regulationsupporting
confidence: 62%
“…Interestingly, it was also observed in this clinical trial that the administration of Rosiglitazone led to lower parasite clearance time 145. This observation might be explained from another study, which showed that Rosiglitazone preferentially increases the expression of CD36 on macrophages146 with minimal effect on endothelial cells148 and this would potentially lead to increased phagocytosis by these cells 149. Taken together, this study shows that targeting inflammatory responses at higher exposures might indeed be protective, but these processes need to be adequately investigated.…”
Section: Taking Advantage Of Immune Regulationsupporting
confidence: 62%
“…This raises a theoretical concern that the use of rosiglitazone, a CD36 upregulator, may lead to a functional increase in endothelial CD36 levels and to cytoadhesion. However, we have previously demonstrated that PPARg agonists appear to have a maximal effect on monocyte and macrophage CD36 expression but only a minimal effect on endothelial surface levels of CD36, and that they do not significantly modify parasitized erythrocyte-endothelial cell interactions in vitro [40]. In summary, PPARg agonists represent a novel class of immunomodulatory drugs that may have utility in the management of inflammatory states such as severe P. falciparum malaria.…”
Section: Discussionmentioning
confidence: 95%
“…Although PPARγ agonists have been shown to upregulate both CD36 and ICAM-1 expression, these agonists had minimal effects on the expression of sequestration receptors on endothelial cells and did not upregulate endothelial cell adhesion of PEs [47]. …”
Section: Discussionmentioning
confidence: 99%